ANALISA KESEHATAN KEUANGAN PERUSAHAAN DENGAN PENDEKATAN ALTMAN Z-SCORE (STUDI PADA PT ASII TAHUN 2020-2023) - Sibarani, Romida Br; Ardella, Prasasti; Lubis, Naomi; Sucipto, Tia Novira (LPPM Universitas Bina Bangsa, 2025)
This study aims to evaluate the financial health of the company by applying the Altman Z-Score approach. The analysis focuses on the financial performance of PT ASII from 2020 to 2023. The data used is sourced from secondary data, obtained through the collection of internal company documents using a document review method. The analytical approach employed is a quantitative method based on the essential formulas within the Altman Z-Score framework. The results of this study indicate that, overall, PT ASII is in a financially healthy condition. This is evidenced by PT ASII's Z-Score, which consistently falls within the healthy category defined in the Altman model. The findings suggest that the company possesses adequate financial resilience and a relatively low potential risk of bankruptcy during the observation period.